SOLDIER DISCIPLINE LAW: A STUDY OF MILITARY LAW AND THE CRIME OF DESERTION - Edwin, Mayor Chk (Faculty of Law Universitas 17 Augustus 1945 Cirebon, 2023)
Crimes committed by members of the TNI are purely military based on regulations related to the military. The crime of desertion is an example of a pure criminal offense committed by the military. The objectives of this study are to (1) To find out the criminal responsibility of a TNI soldier who commits the crime of desertion. (2) To find out the relationship between the Military Criminal Code and the General Criminal Code. The type of research used in the preparation of this thesis is normative juridical research, namely research that relies on legal norms contained in laws and court decisions and norms that exist in society. The data used in this thesis is secondary data supported by primary data, which means secondary data, namely data obtained from library materials where secondary data consists of primary legal materials, secondary legal materials and tertiary legal materials. The data analysis used is a qualitative approach to primary data and secondary data. The results of this study indicate that (1) The application of military law against the perpetrators of the crime of desertion as a member of the Military (TNI) the threat of punishment is more severe than the threat of punishment contained in the Criminal Code (seen as less fulfilling a sense of justice). (2) The relationship between KUHPM and KUHP is inseparable because KUHPM is part of the KUHP. The scientific implication of this research is to provide understanding to the public in general and the military in particular about the existence of criminal liability for military who commit the crime of desertion.